A signaling cascade of nuclear calcium-CREB-ATF3 activated by synaptic NMDA receptors defines a gene repression module that protects against extrasynaptic NMDA receptor-induced neuronal cell death and ischemic brain damage - Zhang, Sheng-Jia; Buchthal, Bettina; Lau, David; Hayer, Stefanie Nicole; Dick, Oliver; Schwaninger, Markus; Veltkamp, Roland; Zou, Ming; Weiss, Ursula; Bading, Hilmar (The journal of neuroscience, 2011)
Synapse-to-nucleus signaling triggered by synaptic NMDA receptors can lead to the buildup of a neuroprotective shield. Nuclear calcium activating the cAMP response element binding protein (CREB) plays a key role in neuroprotection acquired by synaptic activity. Here we show that in mouse hippocampal neurons, the transcription factor Atf3 (activating transcription factor 3) is a direct target of CREB. Induction of ATF3 expression by CREB in hippocampal neurons was initiated by calcium entry through synaptic NMDA receptors and required nuclear calcium transients and calcium/calmodulin-dependent protein kinase IV activity. Acting as a transcriptional repressor, ATF3 protects cultured hippocampal neurons from apoptosis and extrasynaptic NMDA receptor-induced cell death triggered by bath application of NMDA or oxygen-glucose deprivation. Expression of ATF3 in vivo using stereotaxic delivery of recombinant adeno-associated virus reduces brain damage following a cerebral ischemic insult in mice. Conversion of ATF3 to a transcriptional activator transforms ATF3 into a potent prodeath protein that kills neurons in cell culture and, when expressed in vivo in the hippocampus, ablates the neuronal cell layer. These results link nuclear calcium-CREB signaling to an ATF3-mediated neuroprotective gene repression program, indicating that activity-dependent shutoff of genes is an important process for survival. ATF3 supplementation may counteract age- and disease-related neuronal cell loss caused by a reduction in synaptic activity, malfunctioning of calcium signaling toward and within the nucleus (“nuclear calciopathy”), or increases in death signaling by extrasynaptic NMDA receptors.